Poly(malic acid) bearing Doxorubicin and N-Acetyl Galactosamine as a site-specific prodrug for targeting hepatocellular carcinoma. Issue 10 (13th August 2017) - Venkatraj, Nivishna; Nanjan, M. J.; Loyer, Pascal; Chandrasekar, M. J. N.; Cammas Marion, Sandrine
Abstract: In the past, several systems of drug delivery carriers have been designed with a high capacity to target specific cells and/or tissues and a reduced non-specific toxicity. In this context, we synthesized and characterized novel poly(malic acid) derivatives bearing Doxorubicin (Dox), Poly(ethylene glycol) (PEG) and/or N-Acetyl Galactosamine (NAcGal) for drug delivery. These poly(malic acid) derivatives were obtained by chemical modification of the carboxylic acid lateral groups of poly(malic acid) (PMLA). The resulting nanoplatforms were evaluated for their in vitro cytotoxicity using the human HepaRG hepatoma cell line. Results reveal that the PMLA nanoplatform modified with PEG and Dox has an IC50 of 936 nM corresponding to a Dox concentration of 47 nM, while the grafting of NAcGal onto the nanoplatform reduced the IC50 to 527 nM corresponding to a Dox concentration of 26 nM. The presence of the targeting moiety, NAcGal, thus improves the cellular toxicity of the Dox.